A smart grid integration platform developed for monitoring and management of energy systems - Ozbuber, Serdar; Bagriyanik, Mustafa (IEEE, 2015)
This paper presents the Integration, Monitoring and Management Platform (IMMP) developed as a standards based, vendor neutral solution which consists of software application modules and RTUs with IED communications capabilities. IMMP enables integration of the conventional infrastructure with emerging products and technologies, improves monitoring and management capabilities and help transforming the existing infrastructure to Smart Grids (SG) by using the new concepts and standards. IMMP, mainly consists of software application modules and RTUs with embedded software, firmware, drivers and interface modules to communicate with the existing power and energy units and the applications. System data retrieved from all the critical points is validated and recorded in data storage and processed for; displaying the grids' situation on graphical maps, sending alerts to operators, taking automatic actions where applicable and enables analysis of the long term collected data for extracting valuable information to improve efficiency by managing the assets and the workforce more effectively and planning future needs and investments more accurately, which eventually help reducing the costs.